Antivascular Endothelial Growth Factor Agents for Neovascular Age-Related Macular Degeneration. (19th November 2011) - Zampros, Ilias; Praidou, Anna; Brazitikos, Periklis; Ekonomidis, Panagiotis; Androudi, Sofia
Abstract : Age-related macular degeneration (AMD) is the leading cause of severe visual loss and blindness over the age of 50 in developed countries. Vascular endothelial growth factor (VEGF) is considered as a critical molecule in the pathogenesis of choroidal neovascularization (CNV), which characterizes the neovascular AMD. Anti-VEGF agents are considered the most promising way of effectively inhibition of the neovascular AMD process. VEGF is a heparin-binding glycoprotein with potent angiogenic, mitogenic and vascular permeability-enhancing activities specific for endothelial cells. Two anti-VEGF agents have been approved by the US Food and Drug Administration (FDA) for the treatment of neovascular AMD. Pegaptanib sodium, which is an aptamer and ranibizumab, which is a monoclonal antibody fragment. Another humanized monoclonal antibody is currently off-label used, bevacizumab. This paper aims to discuss in details the effectiveness, the efficacy and safety of these three anti-VEGF agents. New anti-VEGF compounds which are recently investigated for their clinical usage (VEGF-trap, small interfering RNA) are also discussed for their promising outcomes.